2018
DOI: 10.1038/s41598-018-35607-w
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal-zone-specific reduction of sensory neuron density in the olfactory epithelium following long-term exercise or caloric restriction

Abstract: Exercise (Ex) and caloric restriction (CR) reduce oxidative stress and improve organ function. For instance, voluntary Ex or CR is known to reduce age-related cochlear damage in male C57BL/6J mice. However, the effect of Ex and CR on the olfactory system is unknown. In this study, we confirmed the positive effect of Ex and CR on age-related cochlear damage, but found that Ex and CR affected negatively cell dynamics in the olfactory epithelium (OE) by reducing the number of mature olfactory sensory neurons (OSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…It is reported that such age-related degenerative changes in the cochlea are reduced by some non-genetic interventions other than PR. For example, long-term voluntary exercise significantly delayed the progression of AHL and reduced OHC loss in the apical turn of the cochlear in aged mice 23,41 . Long-term CR of 10 month duration suppressed apoptotic cell death in the apical turn of the cochlea compared with non-CR mice 23,42 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is reported that such age-related degenerative changes in the cochlea are reduced by some non-genetic interventions other than PR. For example, long-term voluntary exercise significantly delayed the progression of AHL and reduced OHC loss in the apical turn of the cochlear in aged mice 23,41 . Long-term CR of 10 month duration suppressed apoptotic cell death in the apical turn of the cochlea compared with non-CR mice 23,42 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, long-term voluntary exercise significantly delayed the progression of AHL and reduced OHC loss in the apical turn of the cochlear in aged mice 23,41 . Long-term CR of 10 month duration suppressed apoptotic cell death in the apical turn of the cochlea compared with non-CR mice 23,42 . In an analogy with these interventions, PR also had preventive effects on age-related degenerative changes in the OHCs in the apical turn.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations